Exploring the Intersection of Environmental Events and Domestic Political Violence in the United States - Perliger, Arie (Terrorism and political violence, 2022)
Increasing levels of extreme weather patterns and environmental deterioration pose pertinent threats to the availability of essential resources, such as food and water. Past research has found a positive association between climate change and the likelihood of internal conflicts, especially in developing countries. We argue that intensifying climate events can lead to an increase in the spread and intensity of both left and right-wing ideologically motivated violence in developed countries as well, specifically the United States. We also focus on how regional environmental characteristics might be correlated to the geographical distribution of domestic political violence. Our findings suggest that while both far-right and environmental violence are more prevalent during warmer seasons and extreme warming weather events, such as heat waves, political and demographic factors also need to be considered. We also found a strong linkage between man-made ecological damage, as opposed to natural disasters, and the prevalence of eco-violence incidents, especially in states that have a progressive-liberal political culture and high levels of ecological exploitation. We conclude with a brief discussion of findings and suggestions for future research.